The Role of Physical Activity in Gut–Brain Axis Regulation and Cognitive Enhancement in Schizophrenia - Niczyporuk, Patrycja; Zajkowska, Izabela; Warych, Wiktor; Baran, Julia; Wojciechowska, Karolina; Martowska, Julia (Quality in Sport, 2025)
Background: Recent research highlights the growing importance of the gut–brain axis in neuropsychiatric disorders, including schizophrenia. Particular attention is given to microbial dysbiosis and its influence on neurotransmitter dynamics, systemic inflammation, and cognitive function. Schizophrenia is marked by progressive impairments in attention, working memory, and executive function, often accompanied by hippocampal atrophy—deficits not fully addressed by standard pharmacotherapy. Aim: This review aims to elucidate the mechanisms through which gut microbiota influence neurotransmitter synthesis and cognitive regulation in schizophrenia, and to evaluate the role of exercise as a potential modulator of both microbiota composition and neuroplasticity. Material and Methods: A systematic literature review was conducted on March 18, 2025, using a Python-based script to extract relevant studies from PubMed. The search focused on the interactions between schizophrenia, gut microbiota, neurotransmitter systems, and the effects of exercise-based interventions. Results: Evidence from clinical and preclinical studies indicates that alterations in gut microbiota significantly affect the synthesis of neuroactive compounds such as serotonin, GABA, and dopamine. Moreover, structured exercise programs have been shown to improve cognitive function, increase hippocampal volume, and positively modulate gut microbial composition, suggesting synergistic benefits when combined with conventional treatment. Conclusions: Targeted interventions addressing the gut–brain axis—through microbiota modulation and exercise therapy—represent promising adjunctive strategies in the treatment of schizophrenia. These approaches may enhance neurocognitive outcomes and support more personalized, holistic models of care.